Entre a terra e a conquista: petições e sesmarias indígenas na capitania do Siará Grande (1706-1738) - Ribeiro, João Victor Diniz (2025)
This research analyzes 17 land grants (sesmarias) to Indigenous peoples in the Captaincy of Siará Grande between 1706 and 1738, investigating how these groups used the colonial legal order to secure rights over their lands. These sesmarias reveal specific dynamics of territorialization and Indigenous participation in the colonial land tenure system. The study examines Indigenous petitions, their arguments, and their reception by colonial authorities, identifying patterns, regional differences, and negotiation strategies. The research is based on historical sources and employs a theoretical framework that integrates the New Indigenous History and the perspective of law as a normative knowledge system, considering Indigenous peoples as active historical agents and analyzing the interaction between legal norms and local practices. The findings demonstrate that Indigenous groups were not passive agents in the territorial occupation process; rather, they used the available legal structures to seek royal recognition and consolidate their land presence. Although subjected to a subordinate legal status, they strategically leveraged their involvement in military, religious, and economic activities to claim land, forming, in some cases, Indigenous elites that repeatedly resorted to the sesmaria system. The study also highlights how land grants varied according to regional contexts: the Tabajara of Ibiapaba secured individual sesmarias, while the Potiguara, Jaguaribara and Canindé sought collective guarantees or the foundation of settlements. More than mere land letters, sesmarias represented a mechanism for territorial survival and integration into the colonial order, though they did not ensure full security against ongoing disputes. This study contributes to the understanding of legal forms of land appropriation in Portuguese America, emphasizing Indigenous agency and the flexibility of colonial law in its interaction with different groups and territories.